PTU-027 Prophylaxis of Post ERCP Pancreatitis in the UK. have the Esge Created Consensus?. (4th June 2013) - Sinha, A; Hudson, B; Farrant, J M; Linehan, J; Colleypriest, B
Abstract : Introduction: Post ERCP pancreatitis (PEP) occurs in 3.5% of unselected cases 10% of which are severe. PEP is significantly higher in certain patient groups, for example patients with Sphincter of Oddi dysfunction or with a pre-cut sphincterotomy. The 2010 European Society for Gastrointestinal Endoscopy (ESGE) guidelines on PEP prophylaxis recommend routine use of rectal NSAIDs and the insertion of pancreatic stents (PS) in high risk patients 1 . This study surveys UK practise of PEP prophylaxis in view of ESGE guidelines. Methods: 220 ERCPists were invited to complete an online survey concerning their awareness of ESGE guidelines, patient selection for PEP, and use of rectal NSAIDs and insertion of PS. 67 responses from 53 UK hospitals were received (response rate = 30.4%). Results: 79% of respondents were aware of ESGE guidelines, of which 47% had subsequently changed their practise. Only 9% of respondents used PEP for all patients as recommended by the ESGE. The majority (66%) used PEP in selected patients, whilst 25% never used PEP. Choice of PEP is demonstrated in the below table. Concerns relating to ESGE guidelines were expressed in a free text comments sections Conclusion: If this study is representative of wider practise it would suggest there is widespread variation in the administration of PEP in the UK. Only a minority of respondents were adherent to ESGE guidelines, although the majority had considered them. A significant number of departments were in the process of developing separate local guidelines. Stenting otherwise uncannulated pancreatic ducts and NSAID nephrotoxicity were commonly raised reasons for not adopting ESGE guidelines. Given there are currently no UK guidelines for PEP, this may be an opportunistic time for collaboration. A coordinated strategy of national guidelines or research may contribute to creating a consensus in practise across the UK and ultimately reduce the incidence of PEP. Disclosure of Interest: None Declared Reference: European Society of Gastrointestinal Endoscopy (ESGE) Guideline: Prophylaxis of post-ERCP pancreatitis. Dumonceau, J.M., Andriulli, A., Deviere, J., Mariani, A., Rigaux, J., Baron, T.H. & Testoni, P.A. Endoscopy 2010; 42: 503–515.